IFRS financial statements of companies in the extractive industries as a basic tool of financial management - V. E. Gladkova (Путеводитель предпринимателя)
In connection with the official adoption in Russia of international financial reporting standards (IFRS), Russia’s accession to the WTO arises a different meaning of IFRS for Russian companies. The need to position themselves in the global world market where statements are prepared in accordance with IFRS, is only possible using data for all kinds of accounting: financial, managerial, based on IFRS. It’s not a simple question, since Russia is primarily used transformation method.